2002
DOI: 10.1677/joe.0.1720001
|View full text |Cite
|
Sign up to set email alerts
|

GH as a co-gonadotropin: the relevance of correlative changes in GH secretion and reproductive state

Abstract: It is now well established that exogenous GH promotes sexual maturation and reproductive function. The possibility that this may reflect physiological actions of endogenous GH has, however, rarely been considered. Correlative changes in GH secretion and reproductive state (puberty, pregnancy, lactation, menopause and ovarian cycles) are thus the primary focus of this review. GH secretion is, for instance, elevated during major transitions in reproductive status such as puberty and pregnancy. In some cases, aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
0
8

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 214 publications
(125 reference statements)
4
64
0
8
Order By: Relevance
“…The development of preantral follicles has generally been considered to be largely independent of gonadotrophins and pituitary hormones. However, increasing evidence indicates that growth hormone (GH), in addition to having metabolic effects, is involved in the regulation of ovarian functions, including the preantral stage of development (14,17). In vitro studies in immature mice showed a stimulatory effect of GH on preantral follicle development and follicular cell proliferation that is synergistic with IGF-I (15,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The development of preantral follicles has generally been considered to be largely independent of gonadotrophins and pituitary hormones. However, increasing evidence indicates that growth hormone (GH), in addition to having metabolic effects, is involved in the regulation of ovarian functions, including the preantral stage of development (14,17). In vitro studies in immature mice showed a stimulatory effect of GH on preantral follicle development and follicular cell proliferation that is synergistic with IGF-I (15,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing evidence suggests that GH also plays a role in reproductive functions. Recently, GH has been proposed to be a 'cogonadotrophin' in mammals (Hull & Harvey 2002). This idea is supported by the findings that correlative changes in GH secretion can be observed at various stages of the ovarian cycle, sexual maturation, pregnancy, and seasonal breeding (Hull & Harvey 2000a,b).…”
Section: Introductionmentioning
confidence: 90%
“…Em nível ovariano, o GH pode exercer ações sinérgicas com o FSH nas células da granulosa humana para produzir estradiol e progesterona e com LH para estimular a secreção de androgênios tecais (57,58).…”
Section: Eixo Somatotróficounclassified